2017
DOI: 10.1007/s00256-017-2709-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute non-contact anterior cruciate ligament tears are associated with relatively increased vastus medialis to semimembranosus cross-sectional area ratio: a case-control retrospective MR study

Abstract: Acute non-contact ACL tears are associated with increased VM:SM CSA ratios, which may imply a relative deficiency in hamstring strength. This study also demonstrates a novel method of measuring the relative CSA of muscles on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Since we only tested the nondominant leg, our results may be important for athletes from sports that require weight-bearing of the nondominant leg to support actions of the dominant leg, which may lead to greater risk of knee ligament injuries [2,22]. However, recent evidence has indicated that H:Q ratios calculated by PT alone may be weak indicators of future injury incidence in sports [8,39], and that this relationship may also be influenced by other neuromuscular variables, such as RTD, MS, MA, muscle fatigue, and torque produced at multiple angles of ROM [9,11,13,14,15,16,17,21,40,41]. Therefore, because of the multifactorial nature of hamstring strain ACL tears [8,42], increasing traditional and alternative H:Q ratios (based on more than one of these neuromuscular variables) have been proposed as potential strategies for enhancing performance and reducing injury risk [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since we only tested the nondominant leg, our results may be important for athletes from sports that require weight-bearing of the nondominant leg to support actions of the dominant leg, which may lead to greater risk of knee ligament injuries [2,22]. However, recent evidence has indicated that H:Q ratios calculated by PT alone may be weak indicators of future injury incidence in sports [8,39], and that this relationship may also be influenced by other neuromuscular variables, such as RTD, MS, MA, muscle fatigue, and torque produced at multiple angles of ROM [9,11,13,14,15,16,17,21,40,41]. Therefore, because of the multifactorial nature of hamstring strain ACL tears [8,42], increasing traditional and alternative H:Q ratios (based on more than one of these neuromuscular variables) have been proposed as potential strategies for enhancing performance and reducing injury risk [9].…”
Section: Discussionmentioning
confidence: 99%
“…MS increases have been thought to be a primary determinant of strength gains following resistance training [43]. Because of this relationship, a few studies have suggested that a reduced MS H:Q ratio can also indicate an increased knee strength imbalance and potential risk of injury [15,16,17]. For instance, Evangelidis et al [15] demonstrated that quadriceps MS explained about 30% to 31% of CON PT, and that hamstrings MS explained about 48% to 58% of ECC PT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wieschhoff and colleagues [8] measured the cross-sectional areas of both the vastus medialis and the semimembranosus muscles on the highest available axial image of a conventional knee MRI. They demonstrated that in patients who sustained a non-contact tear of the ACL, the quadriceps (vastus medialis) was disproportionately large compared to the hamstring (semimembranosus).…”
Section: Useful Clinical Insightsmentioning
confidence: 99%